2023
DOI: 10.1186/s12877-023-04045-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring variation in implementation of multifactorial falls risk assessment and tailored interventions: a realist review

Abstract: Background Falls are the most common safety incident reported by acute hospitals. In England national guidance recommends delivery of a multifactorial falls risk assessment (MFRA) and interventions tailored to address individual falls risk factors. However, there is variation in how these practices are implemented. This study aimed to explore the variation by examining what supports or constrains delivery of MFRAs and tailored interventions in acute hospitals. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…From the point of view of nursing, the knowledge of risk factors and conditions in which falls are most frequent is of basic importance because it enables the threat to be predicted and preventive measures taken. The National Institute for Health and Care Excellence in England recommends that patients of 65 and older that are hospitalized due to severe diseases, and patients of 50–64 classified in the group of an increased risk of falls should be subject to the multifactorial falls risk assessment (MFRA) and to properly tailored procedures ( 23 , 24 ), in order to solve, improve, or manage their individual fall risk during their hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of nursing, the knowledge of risk factors and conditions in which falls are most frequent is of basic importance because it enables the threat to be predicted and preventive measures taken. The National Institute for Health and Care Excellence in England recommends that patients of 65 and older that are hospitalized due to severe diseases, and patients of 50–64 classified in the group of an increased risk of falls should be subject to the multifactorial falls risk assessment (MFRA) and to properly tailored procedures ( 23 , 24 ), in order to solve, improve, or manage their individual fall risk during their hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The study began with a realist review of falls prevention literature in hospitals (Alvarado et al, 2023). This elicited and refined stakeholders' theories, included within the literature, about how risk assessment and prevention practices work.…”
Section: Methodsmentioning
confidence: 99%
“…A recent realist review of the international literature found that patient participation in their own falls prevention was a key falls prevention strategy (Alvarado et al, 2023). Several studies in the review involved staff-patient partnerships through which risk assessments and care plans were co-produced (Dykes et al, 2020).…”
Section: Introduction and Backg Roundmentioning
confidence: 99%
“…On the other hand, patients are admitted and discharged on the same day, and the fast, busy, and crowded day surgery settings present challenges to comprehensive fall risk assessment (Deng et al, 2019;Jiang et al, 2020). Most fall risk assessment tools have been conducted in general inpatient settings, and there is limited availability of ophthalmic-specific assessment tools while complex ward conditions can disrupt how such tools work as facilitators (Alvarado et al, 2023;Fulbrook et al, 2023). The fall risk assessment needs to be efficient and effective in day surgery settings.…”
mentioning
confidence: 99%